Engineering in Translational Medicine - Cai, Weibo (Springer London : Imprint: Springer, 2014)
This book covers a broad area of engineering research in translational medicine. Leaders in academic institutions around the world contributed focused chapters on a broad array of topics such as: cell and tissue engineering (6 chapters), genetic and protein engineering (10 chapters), nanoengineering (10 chapters), biomedical instrumentation (4 chapters), and theranostics and other novel approaches (4 chapters). Each chapter is a stand-alone review that summarizes the state-of-the-art of the specific research area. Engineering in Translational Medicine gives readers a comprehensive and in-depth overview of a broad array of related research areas, making this an excellent reference book for scientists and students both new to engineering/translational medicine and currently working in this area.